Spatial Genetic Structure and Diversity Reveal Central‐Marginal Patterns in the Rare Freshwater Mussel, Pleurobema riddellii - Alexander S. Zalmat; Matthew Harrison; Brad Littrell; Kyle T. Sullivan; Charles R. Randklev; Timothy H. Bonner; Noland H. Martin (Journal of Biogeography, 2026)
Aim This study sought to evaluate how historical drainage connectivity and contemporary basin isolation have shaped population genetic structure and diversity in an imperilled species of freshwater mussel, Pleurobema riddellii. Location Covers the range of P. riddellii , spanning seven river basins of the Gulf Coastal Plains of the southern USA, including the San Jacinto, Neches, Sabine, Calcasieu, Red, Ouachita and Pearl river systems. Methods A genome‐wide single nucleotide polymorphism (SNP) dataset was generated using a restriction‐site associated DNA sequencing approach. After filtering and assembly, a dataset consisting of 12,062 SNP loci from 351 individuals was retained. Population genetic structure was evaluated using principal components analysis and a Bayesian clustering model, ENTROPY. Genetic differentiation among river basins was quantified using Nei's G ST and patterns of genetic diversity were assessed using observed heterozygosity and Watterson's θ . Results Population genetic analyses revealed structuring that corresponded closely with river basin boundaries. Centrally distributed populations from the Neches, Sabine and Calcasieu basins formed a genetically cohesive group characterised by low genetic differentiation and elevated genetic diversity. Marginal populations from the San Jacinto, Red, Ouachita and Pearl basins exhibited higher levels of genetic differentiation and reduced genetic diversity. Main Conclusions Here, we demonstrate a central‐marginal pattern in genomic structure and diversity across the range of P. riddellii . These results suggest that historical hydrological connectivity, coupled with prolonged isolation and reduced effective population sizes at range margins, likely played a role in shaping standing genomic variation in this system. More broadly, the genomic structure observed in P. riddellii is consistent with other unionid mussels in the region, highlighting the contributions of historical hydrological configurations in structuring freshwater biodiversity.